Analysis of Faculty Teaching using Multi-criteria Decision Making Approach - Ghosh, Dhrubajyoti; Pal, Anita (International Journal of Engineering and Technology, 2018)
In order to maintain a good standardof any college, the institution should follow paperÂ basedÂ approachÂ orÂ web-based approachÂ toÂ gatherÂ studentÂ feedbackÂ onÂ facultyÂ teaching to maintain the qualities of the faculty. Students have very much concerned about their teachers who have played a vital role in their life in both outside or inside of the institutions which helps them to justify a teacher and it comes in form of their feedback. In this paper, we introduce a ranking method of the given feedback's factors of teacher's performances with the help of multi-criteria decision making approach using neutrosophic logic.Â WeÂ useÂ theÂ scoreÂ Â andÂ accuracy functionsÂ andÂ theÂ hybridÂ score-accuracyÂ functionsÂ of singleÂ valuedÂ neutrosophicÂ numbersÂ (SVNNs)Â and rankingÂ methodÂ forÂ SVNNs.Â